Menangkal Faham Radikal Berbasis Pondok Pesantren Bahasa Arab - Mohamad Ma’mun (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2020)
The phenomenon of terrorism action using violence in Muslim radicalism makes jihad the reason for justification as well as a theological foundation. It takes a preventive model of radicalism that continues to propagate in various fields. One of the Pesantren who took part in the prevention of radicalism through educational pathways is Pondok Pesantren Syahamah. The purpose of this research is to describe the concept and process of learning in the Islamic boarding school of Syahamah and to describe the strategy performed by the Islamic boarding school of Shahamah in the ward against radicalism. Using the qualitative method of phenomenology technique is known that Pondok Pesantren Syahamah is a non-formal Islamic education institution that is based on Islam Ahlussunnah wal Jama'ah under the auspices of Yayasan Syahamah. The vision of Pondok Pesantren Syahamah is to be a model and excels in the teaching of religious sciences according to Manhaj Ahlussunnah wal Jama'ah, also in the teaching of Arabic that combines the classical and modern methods. His activities, Syahamah classifies it into several parts: the field of religion, social areas and the economic field. The period of education in Ponpes Syahamah is 3 years, reached in 3 classes, namely the Ula Class (Basic), Wustha Class (intermediate) and ' Ulya (high) class and each class consists of two semesters. The strategy that is used in Pondok Pesantren Syahamah is Tadrij al-Tadris learning, Strategy Model learning Talaqqi and Strengthening mastery science nahwu Sharaf